2011
DOI: 10.1590/s1517-83822011000400026
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors of antibodies against Leptospira spp. in ovines from Uberlândia municipality, Minas Gerais state, Brazil

Abstract: The objectives of the present study were to verify the seroprevalence of anti-Leptospira spp. antibodies, identify the most frequent serovars and the risk factors associated with the infection in Uberlândia, Minas Gerais, Brazil. A total of 334 ovines blood samples were collected in 12 farms from Uberlândia municipality to be evaluated by means the Microscopic Agglutination Test (MAT) against 22 serovars of Leptospira spp.and an epidemiologic questionnaire was applied for each farm in order to correlate with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 6 publications
4
4
1
3
Order By: Relevance
“…Hardjobovis and Autumnalis were the most frequent serovars of sheep and goats found in this study, a result that corroborates the findings of recent serological surveys conducted on small ruminants in Brazil (HERRMANN et al, 2004;LILENBAUM et al, 2007;ARAÚJO NETO et al, 2010;HIGINO et al, 2010;SALABERRY et al, 2011;CARVALHO et al, 2011;SANTOS et al, 2012;MARTINS et al, 2012;MORAES et al, 2012;ALVES et al, 2012;HIGINO et al, 2012;RIZZO et al, 2014). It was long believed that these animals acquired leptospirosis only by prior contact with other species (LEON-VIZCAINO et al, 1987), although the breeding of these species together with cattle breeding and the presence of rodents are important factors for the dissemination of the Hardjobovis and Autumnalis serovars, respectively (FAINE et al, 1999;SALABERRY et al, 2011;SEIXAS et al, 2011).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Hardjobovis and Autumnalis were the most frequent serovars of sheep and goats found in this study, a result that corroborates the findings of recent serological surveys conducted on small ruminants in Brazil (HERRMANN et al, 2004;LILENBAUM et al, 2007;ARAÚJO NETO et al, 2010;HIGINO et al, 2010;SALABERRY et al, 2011;CARVALHO et al, 2011;SANTOS et al, 2012;MARTINS et al, 2012;MORAES et al, 2012;ALVES et al, 2012;HIGINO et al, 2012;RIZZO et al, 2014). It was long believed that these animals acquired leptospirosis only by prior contact with other species (LEON-VIZCAINO et al, 1987), although the breeding of these species together with cattle breeding and the presence of rodents are important factors for the dissemination of the Hardjobovis and Autumnalis serovars, respectively (FAINE et al, 1999;SALABERRY et al, 2011;SEIXAS et al, 2011).…”
Section: Resultssupporting
confidence: 92%
“…The frequency of seropositive sheep in this study was lower than that previously reported for most studies conducted with this species in other Brazilian states: 34.3% in Rio Grande do Sul (HERRMANN et al, 2004), 33.3% in Rondônia (AGUIAR et al, 2010, 22.0% in Minas Gerais (SALABERRY et al, 2011), 47.4% in Rio de Janeiro (MARTINS et al, 2012), and 22.8% in São Paulo (RIZZO et al, 2014). However, these frequencies were higher than those found in surveys conducted in the Northeast region: 3.5% in Rio Grande do Norte (AZEVEDO et al, 2004) and 7.5% in Paraíba (HIGINO et al, 2010).…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…infection. SALABERRY et al (2011) reported statistical differences among sheep breeds, and purebred animals were more susceptible to infection than Table 1 -Results of serology, polymerase chain reaction (PCR), and bacterial culture of positive animals, according to their origin. mixed-breed animals.…”
Section: Discussionmentioning
confidence: 99%
“…In small ruminants, breed has also been found to be a risk factor associated with leptospirosis (SALABERRY et al, 2011;SANTOS et al, 2012;SILVA et al, 2012). Therefore, the purpose of this study was to detect Leptospira spp.…”
Section: Microbiologymentioning
confidence: 99%